An Autoethnographic Report on the Use and Impact of Social Networking Sites as an Approach to Teaching of the Research Process - Almighty C. Tabuena (Universitas Lampung, 2021)
The establishment of the K-12 curriculum has had a significant impact on subject requirements related to the outcome-based education plan and the requisite output for a given research report or requirement. Social networking platforms enable students to effortlessly complete a variety of tasks, such as learning and performance. By intervening in research, social networking sites break down the barriers that limit both students and teachers in the research process. Three methodologies or ideas have arisen, known as approaches, that could help you facilitate teaching research, even if you are not in the research discipline: the Facebook-Personality Network Approach, the Virtual Research Journal, and the Google Immersion Approach. It is considered favorably by some students and users, but there are those who take advantage of its negative aspects. Instead of focusing on the emerging ideas or topics created by coding, I used social networking sites to demonstrate that research can be done anytime, anyplace, for any purpose or cause. According to the outcome-based education paradigm, students found the three techniques highly engaging. In order to be a teacher-researcher, you must utilize your originality and resourcefulness when it comes to all of the resources, devices, and technology, as well as the available social networking sites.Keywords: approach, impact, research process, social networking sites, teaching DOI: http://dx.doi.org/10.23960/jiip.v3i2.23267